Flowchart of elderly care victms of abuse: an interdisciplinary perspective - Bruna Oliveira Plassa; Miriam Fernanda Sanches Alarcon; Daniela Garcia Damaceno; Viviane Boacnin Yoneda Sponchiado; Luzmarina Aparecida Doretto Braccialli; Janaina Aparecida Vantin Elias da Silva; Maria José Sanches Marin (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To identify the flows of service for older people, victims of violence in different care services and to analyze the main critical issues. Method: This is a descriptive and exploratory study based on interviews with professionals responsible for: health services; judicial and social care, and with elder abuse victims, in a medium-sized city in the countryside of the state of São Paulo. Data enabled the creation of a flowchart to describe and define the critical issues, according to the model created by Franco and Merhy. Results: The following critical issues were identified: lack of centrality when directing complaints; difficulty to contact 100 hotline; collection of insufficient data on the event; lack of communication among services; victim's withdrawal in the middle of the process; lack of knowledge by the services and the population on social care functions; conflict among services in cases of difficult situations to solve, and lack of intervention by primary health care teams in response to a violence complaint. Conclusions and implications for practice: Critical issues point to the need to enhance interventions from the intersectoral perspective, with the aim to improve older people's quality of health.